(untitled) (GYMNASIUM, 2008)
Starting with 2009, the Aerobic gymnastics’ Code of Points suffers a series of modifications in the contents of most of the chapters. The most radical change is effected in the scoring of the artistic component of an aerobic gymnastic exercise. In this, from 5 scoring criteria remain only 3. The most spectacular intervention is suffered by the constructions for the mixt pairs, trio and group. Starting with 2009, it will be allowed, in the aerobic gymnastics constructions, to use elements from acrobatic gymnastics. The actual scoring chart forbuds using these in any moment but the final construction. The restriction regarding boosting the temmates is still enforced, as is the one regarding the execution of acrobatic elements on the ground.